Interactive fuzzy programming for two-level linear fractional programming problems with fuzzy parameters - Sakawa, Masatoshi; Nishizaki, Ichiro; Uemura, Yoshio; Kubota, Keiichi (Electronics & communications in Japan. Part 3, Fundamental electronic science, 2000)
This paper considers the two‐level linear fractional programming problem with fuzzy parameters, which includes the ambiguity of the human expert concerned with formulation of the problem, and proposes an interactive fuzzy programming procedure to cope with the problem. The proposed procedure is as follows. The fuzzy goal is specified for the objective function for the decision‐maker at each level. The minimum tolerance for satisfaction is defined subjectively by the decision‐maker at the upper level. The satisfaction ratio between the levels is considered, and the minimum tolerance of the decision‐maker is modified interactively, if necessary. Then, the satisficing solution is efficiently derived, achieving the balance between the satisfactions at different levels, while emphasizing the intention of the decision‐maker at the upper level. Lastly, the validity and the effectiveness of the proposed method are shown by numerical examples. © 2000 Scripta Technica, Electron Comm Jpn Pt 3, 83(10): 82–90, 2000